Thermal stability and energetics of 15-mer DNA duplex interstrand crosslinked by trans-diamminedichloroplatinum(II) - Hofr, Ctirad; Brabec, Viktor (Biopolymers, 2005)
The effect of the location of the interstrand cross-link formed by trans-diamminedichloroplatinum(II) (transplatin) on the thermal stability and energetics of 15-mer DNA duplex has been investigated. The duplex containing single, site-specific cross-link, thermodynamically equivalent model structures (hairpins) and nonmodified duplexes were characterized by differential scanning calorimetry, temperature-dependent uv absorption, and circular dichroism. The results demonstrate that the formation of the interstrand cross-link of transplatin does not affect pronouncedly thermodynamic stability of DNA: the cross-link induces no marked changes not only in enthalpy, but also in "reduced" (concentration independent) monomolecular transition entropy. These results are consistent with the previous observations that interstrand cross-links of transplatin structurally perturb DNA only to a relatively small extent. On the other hand, constraining the duplex with the interstrand cross-link of transplatin results in a significant increase in thermal stability that is primarily due to entropic effects: the cross-link reduces the molecularity of the oligomer system from bimolecular to monomolecular. Importantly, the position of the interstrand cross-link within the duplex modulates cooperativity of the melting transition of the duplex and consequently its thermal stability.
Keywords: vysoká teplota; reagencia zkříženě vázaná; diferenciální skenovací kalorimetrie; Oligonucleotides; biopolymery; molekulární struktura; Circular Dichroism; Spectrophotometry, Ultraviolet; cirkulární dichroismus; Cross-Linking Reagents; Calorimetry, Differential Scanning; Molecular Structure; oligonukleotidy; Biopolymers; Hot Temperature; DNA; spektrofotometrie ultrafialová; cisplatina; Cisplatin; termodynamika; Thermodynamics